Ultrathin S-doped MoSe2 nanosheets for efficient hydrogen evolution - Xu, Chen (2014)
We report the synthesis of ultrathin S-doped MoSe2 nanosheets demonstrating enhanced HER catalysis with a low onset overpotential of 90 mV and a Tafel slope of 58 mV per decade. We attribute the improved catalytic effects to the proliferation of unsaturated HER active sites in MoSe2 resulting from S-doping.